Four-Layer Tunable Wideband Electromagnetic Shield Based on Cold Plasma - Meilin Liu (IEEE Access, 2020)
In this paper, we present a four-layer tunable wideband electromagnetic shield based on cold plasma. It consists of two dielectric matched layers, one backside housing dielectric layer and one vacuum chamber in between where cold plasma can be produced through a glow discharge. No plasma is produced within the vacuum chamber when low-power communication signal impinges on the shield and it can easily propagate through with very low return and absorption loss. When a high-power microwave pulse impinges on the shield, cold plasma can be timely produced within the chamber to reflect and absorb the high-intensity microwave energy. Input impedance, standing wave ratio, transmission and reflection coefficients and shielding effectiveness for proposed four-layer structure electromagnetic shield are deduced and formulated. Transparent mode of the electromagnetic shield for communication frequency at 3.5GHz is developed based on transmission line and plane wave theory. Simulation results show that the transmission coefficient is close to unity, and the reflection coefficient is near to zero. The half-power transmission bandwidth is 16% for proposed structure with central communication frequency of 3.5GHz. The impact of plasma frequency and plasma collision frequency on the absorption, reflection, shielding effectiveness for interference frequency between 0-6GHz are investigated. Simulation results show that higher the plasma frequency, better the shielding effectiveness is in the investigated frequency band when plasma collision frequency is fixed. It was also demonstrated that the shielding effectiveness of proposed structure can be tuned by changing plasma collision frequency.